Allelic dropout in the endoglin (ENG) gene caused by common duplication beyond the primer binding site - Shestak, Anna G.; Rumyantseva, Victoria A.; Zaklyazminskaya, Elena V. (Frontiers in Genetics, 2025)
Allelic dropout (ADO) is a common limitation of all PCR-based molecular diagnostic methods, leading to false-negative or false-positive results, depending on the allele that was dropped. We report a case of multiple locus-specific allele dropouts mediated by a common duplication beyond the primer-binding site of the endoglin (ENG) gene. We observed a family with hereditary hemorrhagic telangiectasia (HHT) where the HHT diagnosis in the proband (female, 71 years old) and two family members was based on the Curaçao criteria. A nonsense heterozygous c.831C>A (p.Y277*) mutation and a common homozygous duplication c.991+21_26dup in exon 7 of the ENG gene was revealed in the proband. Discrepancies were found between the obvious clinical HHT phenotypes of the two family members and the negative results of cascade familial screening based on capillary Sanger sequencing with classically designed oligoprimers. In addition, ADO was suspected due to the absence of c.991+21_26dup. We analyzed the primer-binding sites using gnomAD to reveal the cause of ADO. Amplicons with notable ADO were resequenced using alternative oligoprimers. Three primer pairs that were designed more distal (toward the 3′-end) after duplication were unable to amplify both alleles. Redesigning oligoprimers complementary to the narrow area successfully detected the heterozygous variant p.Y277* in two family members. The classical primer design for Sanger sequencing may lead to the inefficient amplification of exon 7 amplicons with duplications (up to 19% according to MAF in gnomAD). These results suggest that indels beyond the primer-binding sites may lead to allele loss and false-negative results in DNA diagnostics.